PREDICAMENT OF IMPLEMENTATION OF INTERNATIONAL SYSTEM OF PLANT VARIETY PROTECTION IN INDIA: A COMPARATIVE STUDY - Fareedunnisa Huma, Urvi Shrivastava (International Journal of Modern Agriculture, 2021)
India has been introduced to Intellectual Property Rights (IPR) from the time of the British rule. However, IPR laws were gradient internationally which caused trade tariffs to sky rocket and hindered the process of globalization. Developing countries such as India were forced to use a protectionist form of economy to protect local innovations and pave their growth. India became a signatory to the TRIPS in 1995 and which states that all member states are required to protect plant variety through patents or a ‘sui generis’ system. India formulated the Protection of Plant Variety and Farmer Rights Act, 2001 (PPV&FR) for this purpose. The TRIPS Agreement also impelled international conventions such as the Union of the Protection of New Varieties of Plants (UPOV) which was designed to promote genetically uniform industrial agriculture and was in compliance with WTO’s agenda of trade maximisation. The convention provides a monopoly of rights to breeders and excludes the farmers.Developedcountries gladly accepted the UPOV regime, but for developing nations it was not the most favourable system to be implemented. Through this paper authors are going to analyse the conflict between UPOV and implementation of farmer rights vis-à-vis variance in the requirement of Intellectual Property laws by developed and developing nations and the need to achieve a balance between Intellectual Property Rights and farmer’s right, furthermore, we will be looking into the impact of implementation of Seed Bill in India, under the light of the same.